GOVERNANCE AND INSECURITY IN NIGERIA: AN INTERROGATION, (1999–2024) - Anda Usman Obansa; Terkimbi Dominic Tom (International Studies Journal)
This study critically interrogates the intricate relationship between governance and insecurity in Nigeria from 1999 to 2024, a period marked by democratic transitions and persistent security challenges. Despite the return to civilian rule in 1999 and successive administrations' commitment to democratic governance, Nigeria has witnessed a dramatic escalation in insecurity, including insurgency, banditry, kidnapping, herder-farmer conflicts, and secessionist agitations. Using a qualitative-descriptive methodology and drawing insights from secondary data sources such as policy documents, media reports, and scholarly literature, the study examines how weak institutions, poor service delivery, widespread corruption, political exclusion, and leadership failures have contributed to the state's inability to effectively address insecurity. The findings reveal that insecurity in Nigeria is not merely a function of violent extremism or criminality but is deeply rooted in structural and governance deficits that erode citizens’ trust and widen the gap between the state and society. It also establishes a correlation between poor governance practices such as elite capture of state resources, ethno-religious politicization, and neglect of youth empowerment and the rise in violent resistance and criminal networks. The paper recommends holistic and inclusive governance reforms, strengthening of democratic institutions, community policing, and proactive engagement with marginalized groups as key strategies to address insecurity. By linking governance failures with the prevalence of insecurity, the study contributes to literature on peacebuilding and state resilience in transitional democracies, and provides practical lessons for policymakers, development practitioners, and scholars concerned with Nigeria’s democratic consolidation and national security.